Variasi spasial temporal hidrogeokimia dan sifat aliran untuk karakterisasi sistem kaerst dinamis di sungai bawah tanah Bribin Kabupaten Gunung Kidul DIY - ADJI, Tjahyo Nugroho ([Yogyakarta] : Universitas Gadjah Mada, 2010)
This research is conducted in karst area, which is particularly enclosed by Bribin Underground River Catchment, Gunungkidul Regency. The objectives of this study are: (1) to understand spatial and temporal variation of flow characteristic as well as Diffuse Flow Proportion (PAD) of Bribin River; (2) to assess hydrogeochemistry and to recognize the relationship between hydrogeochemistry and flow characteristics of Bribin River, and (3) to define water agressivity of Bribin River with respect to carbonate mineral and to express the components of Karst Dynamic System (KDS) one-year behavior. To define flow characteristic and PAD, three water level data loggers are installed within upper, lower and the leakage point along Bribin River continued by discharge measurement with the purpose of attaining stage-discharge rating curve. Afterwards, PAD is defined by conducting digital filtering baseflow separation approach after calculation of diffuse, fissure, and conduit recession constant. Next, to figure out hydrogeochemical condition, 120 sample of karst water are analyzed including rain, underground-river, and drip water. After that, scatter plots between hydrogeochemical parameters are conducted to achieve the correlation between PAD and hydrogeochemistry as well as to figure out hydrogeochemical processes to occur. Subsequently, Saturation Indices analysis with respect to calcite mineral and KDS components correlation is carried out to define karst water agressivity and its manners along flowpath of Bribin River. The research’s result demonstrates that there is spatial and temporal differentiation of flow characteristics along Bribin River attributable to the comportment of karst aquifer toward discharging its diffuse, fissure, or conduit flow components, which consequence to the dissimilarity of PAD distribution along Bribin River. Accordingly, PAD characteristics result to dry season hydrogeochemical condition of Bribin River. However, wet season hydrogeochemical condition is more influenced by means of dilution by precipitation process within flood events, which exaggerates CO2 content of water. Generally, the upper-stream cave tend to more aggressive in dissolving limestone, contrast to down-steam cave that be inclined to precipitate carbonate mineral as a result of their differentiation of cavities configuration. In addition, down-stream cave is characterized by open system cavities, subsequent to the CO2 discharge to preserve dissolution process.